2008
DOI: 10.3354/dao01898
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Panulirus argus Virus 1 (PaV1) in juvenile spiny lobsters Panulirus argus from the Caribbean coast of Mexico

Abstract: Macroscopic evidence, histological sections, transmission electron microscopy (TEM) evaluation, and PCR analyses of 25 apparently diseased juvenile spiny lobsters Panulirus argus from the reef lagoon of Puerto Morelos, Mexico, showed the presence of Panulirus argus Virus 1 (PaV1). Cowdry Type A intranuclear viral inclusions were observed in histological analyses, icosahedral viral particles were observed by TEM, and PCR using specific primers for PaV1 amplified a fragment of 499 bp. This is the first report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…PaV1 prevalence in nature is independent of lobster density over the small spatial scales in which lobsters interact (i.e. 10s of meters) (Behringer 2003, LozanoÁlvarez et al 2008. However, the size and dimensions of a shelter may affect the frequency of shelter cohabitation as healthy lobsters co-occur more frequently with diseased lobsters in large casitas (21.7 to 29.4%) than in smaller natural shelters (3.5%) (LozanoÁlvarez et al 2008).…”
Section: Avoidance Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…PaV1 prevalence in nature is independent of lobster density over the small spatial scales in which lobsters interact (i.e. 10s of meters) (Behringer 2003, LozanoÁlvarez et al 2008. However, the size and dimensions of a shelter may affect the frequency of shelter cohabitation as healthy lobsters co-occur more frequently with diseased lobsters in large casitas (21.7 to 29.4%) than in smaller natural shelters (3.5%) (LozanoÁlvarez et al 2008).…”
Section: Avoidance Of Diseasementioning
confidence: 99%
“…10s of meters) (Behringer 2003, LozanoÁlvarez et al 2008. However, the size and dimensions of a shelter may affect the frequency of shelter cohabitation as healthy lobsters co-occur more frequently with diseased lobsters in large casitas (21.7 to 29.4%) than in smaller natural shelters (3.5%) (LozanoÁlvarez et al 2008). Computer simulations using a spatially explicit, individual-based lobster re cruitment model (Butler 2003, Butler et al 2005, Dolan & Butler 2006) altered for modeling benthic disease dynamics in the Florida Keys have also indicated that the avoidance of infected lobsters by healthy lobsters is effective in dampening the prevalence of PaV1 in the population modeled (Dolan 2010).…”
Section: Avoidance Of Diseasementioning
confidence: 99%
“…Although these 2 reports may have just been coincidental, considering that they came shortly after the discovery of P. argus Virus 1 (PaV1), the first naturally occurring viral pathogen found infecting any lobster (Shields & Behringer 2004), further investigation was warranted. PaV1 has been well described in the Florida Keys (Behringer et al 2006 and along the Caribbean coast of Mexico (Huchin-Mian et al 2008). Given the importance of P. argus to recreational and commercial fisheries and the increased awareness of disease generated by reports of PaV1, we anticipate that fishers will more likely report incidences of microsporidiosis if it is indeed increasing in prevalence and emerging as a pathogen of concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discovery of the pathogenic virus Panulirus argus Virus 1 (PaV1) [11], is becoming a major concern, because it could affect negatively P. argus fisheries; this double stranded DNA virus causes a progressive and detrimental infection that ends in death of juvenile lobsters. In experimental infections with P. argus juveniles, PaV1 infected lobsters show lethargy, morbidity, "milky" hemolymph, lack of hemolymph coagulation, and suppression of molt in a range of 30 to 80 days post infection [12]. In the field, PaV1 infected lobsters are recognized by local fishermen as "milky lobsters".…”
Section: Introductionmentioning
confidence: 99%
“…PaV1 is more prevalent in juveniles. This prevalence decreases in sub-adults and adults and clinical signs characteristic of PaV1 are difficult to evaluate in the field [12]. PaV1 is highly prevalent throughout the Caribbean region and its propagation could impact P. argus fisheries [2] [10] [12]- [15].…”
Section: Introductionmentioning
confidence: 99%